Revisiting tuberculous pleurisy: pleural fluid characteristics and diagnostic yield of mycobacterial culture in an endemic area. Issue 9 (21st March 2012) - Ruan, Sheng-Yuan; Chuang, Yu-Chung; Wang, Jann-Yuan; Lin, Jou-Wei; Chien, Jung-Yien; Huang, Chun-Ta; Kuo, Yao-Wen; Lee, Li-Na; Yu, Chong-Jen J
Abstract : Background: Tuberculous pleurisy is traditionally indicated by extreme lymphocytosis in pleural fluid and low yield of effusion culture. However, there is considerable inconsistency among previous study results. In addition, these data should be updated due to early effusion studies and advances in culture methods. Methods: From January 2004 to June 2009, patients with tuberculous pleurisy were retrospectively identified from the mycobacteriology laboratories and the pathology and tuberculosis registration databases of two hospitals in Taiwan where tuberculosis is endemic. Pleural fluid characteristics and yields of mycobacterial cultures using liquid media were evaluated. Results: A total of 382 patients with tuberculous pleurisy were identified. The median lymphocyte percentage of total cells in pleural fluids was 84% (IQR 64–95%) and 17% of cases had a lymphocyte percentage of <50%. The lymphocyte percentage was negatively associated with the probability of a positive effusion culture (OR 0.97; 95% CI 0.96 to 0.99). The diagnostic yields were 63% for effusion culture, 48% for sputum culture, 79% for the combination of effusion and sputum cultures, and 74% for histological examination of pleural biopsy specimens. Conclusion: The degree of lymphocyte predominance in tuberculous pleurisy was lower than was previously thought. The lymphocyte percentage in pleural fluid was negatively associated with the probability of a positive effusion culture. With the implementation of a liquid culture method, the sensitivity of effusion culture was much higher than has been previously reported, and the combination of effusion and sputum cultures provided a good diagnostic yield.